Evaluasi Program Mobil Keliling dalam Meningkatkan Pelayanan Wajib Pajak di Kantor Sistem Administrasi Manunggal Satu Atap Kota Surabaya Utara - Diaz Putra Prakoso; Supri Hartono; M Kendry (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study evaluates the Mobile Samsat Car Program in North Surabaya using the CIPP (Context, Input, Process, Product) model to assess the program's effectiveness in improving motor vehicle tax services. A qualitative method was applied, involving observation, interviews, and documentation analyzed descriptively. The context evaluation revealed that the program emerged due to the rising number of vehicles and limited public access to the main Samsat office. The input analysis showed limitations in human resources, operational vehicles, and service facilities, which hinder the delivery of inclusive public services. In the process aspect, the program showed commendable efforts in reaching the public, but coordination issues among agencies and lack of public outreach led to low participation. Regarding the product, the program has yet to significantly enhance taxpayer awareness and compliance. Overall, the CIPP evaluation indicates that while the Mobile Samsat Car Program is a relevant innovation responding to public needs, it still faces several implementation and outcome challenges. To optimize its impact, improvements are needed in resource availability, service processes, and public education strategies. With continuous development guided by evaluation findings, the program holds strong potential to offer effective, accessible, and efficient tax services across all social levels in Surabaya.